Case report: a co-occurring case of severe Mycoplasma pneumoniae pneumonia and Anti-IgLON5 antibody-associated encephalitis in a pediatric patient - Ye, Zimao; Chen, Yuequn; Tian, Xin (Frontiers in Medicine, 2024)
This case report details the clinical course of a 16-year-old female student with Mycoplasma pneumoniae infection complicated by autoimmune encephalitis, spanning from 6 February 2022, to 12 April 2022, with a one-year follow-up. The patient presented with a two-week history of cough and fever, followed by altered consciousness and neuropsychiatric symptoms, including hyperactivity and incoherent speech. Despite normal brain MRI findings, cerebrospinal fluid (CSF) analysis confirmed Mycoplasma pneumoniae with titers of, and positive IgLON5 antibodies. Initial treatment included azithromycin, ceftriaxone, and acyclovir, followed by mechanical ventilation and ECMO due to respiratory failure. The antibiotic regimen was switched to intravenous omadacycline based on genetic testing results. Autoimmune encephalitis was managed with intravenous methylprednisolone, intravenous immunoglobulin (IVIG), and plasma exchange. The patient’s condition improved, and she was discharged on 12 March 2022, with normal cognitive and behavioral functions. However, she was readmitted one month later due to cognitive decline and sleep disturbances, with a Mini-Mental State Examination (MMSE) score of 20/30 and a modified Rankin Scale (mRS) score of 3. At the one-year follow-up, her MMSE score had improved to 28/30, and her mRS score was 1. This case underscores the importance of comprehensive diagnostic approaches and personalized treatment strategies in managing complex cases of mycoplasma-related infections and associated autoimmune conditions.